(untitled) (Scientiae Studia, 2010)
We reconstruct physiological theory starting from the initial experiences of Claude Bernard - its paradigmatic exemplar - using a modified version of the structuralistic conception of theories, which characterises them by its exemplars, and not by its models, as it happens in the standard version. We preserve the structuralistic distinction between non theoretical and theoretical elements, and we stablish the relationships between the different exemplars of physiology, and between them and the exemplars of biomedical theories. After that, and as a natural consequense of the reconstruction, we describe the mechanisms of physiology, a metatheoretical analytical approach proposed by some philosophers particularly interested in biomedical disciplines. We will argue - after exposing such position - that a better understanding of biomedical knowledge is obtained by the structural analysis of its theories, and that focusing only on the notion of mechanism is unnecessarily limiting.